Prevention and control of Viral Respiratory Tract Infections in populations deprived of liberty - Oliveira, Thaís Barbosa de; Rodrigues, Lorrany Santos; Silva, Caroliny Victoria dos Santos; Santos, Pâmela Jesus dos; Hirata, Maurício Yukio; Santos, Jade Christinne da Costa de Paula dos; Ruy, Maria Beatriz (Revista Prevenção de Infecção e Saúde, 2023)
Introduction: One of the main causes of morbidity and mortality in the world, in populations of all age groups are caused by Viral Respiratory Tract Infections (VRTI), however, there are risk groups in which the condition can be aggravated, as the Population Deprived of Liberty (PDL). Aim: To identify the scientific production on strategies for prevention and control of outbreaks of VRTI in Populations Deprived of Liberty (PDL). Outlining: Medline, Pubmed Central, SCIELO, LILACS and Science Direct databases were used for data collection. Results: 387 articles were found. Of these, 20 addressed aspects related to the theme and only 16 presented a description of coping strategies for the infections addressed. The articles were categorized by content analysis by the Bardin method. Five categories were obtained: Monitoring the Health Situation of PDL (94%, n=15), Social Distancing (75%, n=12), Health Education (37%, n=6), Respect for Human Rights (25%, n=4) and Environmental Hygiene (19%, n=3). Implications: The implementation of these strategies depends on strengthening health systems, supporting the effectiveness of human rights and including the prison health agenda in the public health agenda not only in pandemic periods.